Pengaruh Influencer Media Sosial Instagram terhadap Niat Beli Konsumen Produk Scarlett yang Dimediasi oleh Kredibilitas - Sabella, Ressa Yolanda; Trianasari, Nurvita (IPM2KPE, 2024)
This study aims to explore the influence of Instagram social media influencers on consumer purchase intentions of Scarlett products, with influencer credibility as a mediating variable. A quantitative approach with descriptive and causal methods was used in this study. Data analysis was carried out using SmartPLS 4.0. The results showed that influencer credibility significantly mediates the relationship between the influence of social media influencers and consumer purchase intentions of Scarlett products. Conclusion, 1) Respondents rated the variables of Instagram social media influencers, influencer credibility, and purchase intentions of Scarlett products in the good category. 2) Instagram social media influencers have a positive and significant influence on consumer purchase intentions of Scarlett products. 3) Influencer credibility also has a positive and significant influence on purchase intentions. 4) Influencer credibility effectively mediates the positive influence of Instagram social media influencers on consumer purchase intentions of Scarlett products. Keywords: Social Media Influencers, Credibility, Purchase Intention